Are mindfulness treatments effective for pain in cancer patients? A systematic review and meta‐analysis. (12th August 2021) - Feng, Beibei; Hu, Xiaoqian; Lu, William W.; Wang, Yuling; Ip, Wing‐Yuk
Abstract: Background and objective: Mindfulness‐based interventions (MBIs) have been recently applied in pain management and cancer care. However, inconsistencies exist concerning the effectiveness of MBIs on pain control among cancer patients. Therefore, this study aimed to examine the efficacy of MBIs on pain in cancer patients via a systematic review and meta‐analysis of randomized controlled trials (RCTs). Methods: Databases (MEDLINE, PubMed, Embase, CINAHL, PsycINFO, Cochrane Central Register of Controlled Trials and ClinicalTrials.gov) were searched using key terms related to pain, cancer and mindfulness. The primary outcome was pain intensity. Standardized mean difference (SMD) of each outcome with 95% confidence interval (95% CI) was calculated. The quality of evidence was assessed by GRADE assessment. Results: Ten RCTs with 843 participants were included. Significant pooled effects of MBIs on pain intensity were found at both short‐term (SMD = −0.19, 95% CI [−0.33 to −0.04]) and long‐term (SMD = −0.20, 95% CI [−0.35 to −0.05]) follow‐up, whereas no significance was observed for pain interference. In subgroup analyses, significant intervention effects were only seen in clinic‐based MBIs compared to remote MBIs, and pooled effects of MBIs in attenuating pain were discovered relative to passive rather than active comparators. GRADE ratings showed moderate certainty of evidence in MBIs for pain intensity but low for pain interference. Conclusions: The efficacy of MBIs in reducing pain intensity among cancer patients was revealed in this meta‐analysis, albeit with a small effect size. Future research is warranted to optimize mindfulness treatment for pain control in cancer patients with high methodological quality and a large sample size. Significance: The effect of MBIs on pain in cancer patients was demonstrated in our analysis, albeit with small effect sizes. High‐quality RCTs are needed to verify the efficacy of MBIs on cancer patients or survivors with pain complaints. Future trials should take into account the specific pain outcome measures (pain intensity or pain interference), the approach of intervention provision (clinic‐based or remote MBI, group or individual practice), the duration and frequency of interventions and the comparators (passive or active control arms).